ENGINEERING THE NaYF4:Yb3+/Tm3+ UPCONVERSION NANOPARTICLE LUMINESCENCE ENERGY TRANSFER FOR A RATIOMETRIC pH INDICATOR - Nhat Nam Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
Fluorescent dye 8-hydroxypyrene-1,3,6-trisulfonic acid (HPTS) is used to develop a ratiometric pH indicator based on NaYF4:Yb3+/Tm3+ upconversion nanoparticles (UCNPs). HPTS was functionalized onto the UCNP surfaces via a modified co-condensation silica coating (UCNP@SiO2-HPTS). The as-prepared UCNP@SiO2-HPTS core-shell nanostructure was characterized with transmission electron microscopy, scanning electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy (FT-IR), and photoluminescence spectroscopy. Luminescence resonance energy transfer (LRET) from NaYF4:Yb3+/Tm3+ UCNP to HPTS was found to exhibit pH-sensitivity simultaneously under near-infrared (NIR) irradiation (λ = 980 nm).